ANALISIS SIFAT SMOOTHING RETURN PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2010-2014) - SETIANA, LUCKY (Jurnal Akuntansi AKUNESA, 2015)
ABSTRACTSmoothing returns is a process of income smoothing that net income generated each period not fluctuated too high or too low so that with the average net income for each period will attract investors. Smoothing returns are divided into two types, namely natural smoothing return and intentional smoothing return. The purpose of this study was to determine differences in dividend growth and corporate value among companies doing natural smoothing return and intentional smoothing return. The study was conducted in the banking sector listed on the Indonesia Stock Exchange (BEI) 2010-2014. This research is using purposive sampling and obtained 36 companies as a sample. The analysis technique used was Mann Whitney U test. The results showed that the banking sector is more likely perform natural smoothing return than intentional smoothing return. There is a difference between dividend growth for natural smoothing return and intentional smoothing return companies and there is no difference between corporate value for natural smoothing return and intentional smoothing return companies.Keywords: Smoothing Return, Dividend Growth, Value Company